Family Support and Loneliness Levels among Elderly People at Posyandu - Gulo, Estifania Anggrening; Sianturi, Sondang Ratnauli (Jurnal Keperawatan Florence Nightingale, 2025)
Elderly conditions that experience various declines or deterioration of biological and psychological functions can affect mobility and social contact, one of which is loneliness. The elderly need a family to understand their condition, to be a good listener to meet their needs. This study aims to determine the relationship between family support and the level of loneliness in the elderly. This study was conducted at the Rw 2 Posyandu, Johar Baru Village, Jakarta, September 2024 - February 2025. The study used a cross-sectional design with a quantitative method with a sample of 72 elderly people. The data collection tool used a family support questionnaire that had been tested for validity and reliability with a Cronbach alpha value of 0.881, meaning ‘acceptable reliability’, and the UCLA Loneliness Scare version 3 questionnaire. The results showed that the majority of elderly people had high emotional support 94.4%, high esteem support 79.2%, high instrumental support 94.4%, high information support 93.1%, and high overall family support 94.4%. The level of loneliness for the elderly is high at 52.8%. There is a relationship between emotional support (p-value 0.040), appreciation support (p-value 0.001), instrumental support (p-value), and family support (p-value 0.040) and loneliness, but there is no relationship between information support and loneliness (p-value 0.109). Suggestions for elderly respondents are expected to maintain good relations with their families and continue to inform their families regarding the needs they need